Immunopathogenesis of ocular toxoplasmosis and implications for treatment (2023)
Introduction: Ocular toxoplasmosis appears after primary infection or during the reactivation of chronic infection by the protozoa Toxoplasma gondii. The risk of ocular involvement and the heterogeneity of clinical manifestations, their complications, and the probability of recurrences are linked to polymorphisms in immune response-related genes, cytokine networks, lymphocyte subpopulation, and parasite virulence factors. Appropriate clinical management and evidence-based advisory recommendations for patients require a clear understanding of the immunopathological mechanisms of this parasitic disease.Areas covered: Narrative review of the scientific literature in human ocular toxoplasmosis related to parasitological and immunological characteristics, genetic polymorphisms linked to ocular involvement, and the clinical correlations of the cytokinome in aqueous humor and experiments with peripheral blood mononuclear cells.Expert Opinion/Commentary: The greater severity in people infected by South American strains is partly explained by parasite protein kinases interfering with the effector immune functions of inter-feron-gamma, resulting in lower antiparasitic activity and more significant inflammation. Future thera-pies should point to the increase in IFN-? production (for example, by stimulating CD4+ memory T cells subset). Thus, immune-based interventions could be promising in inducing an appropriate response for treating and preventing ocular damage and recurrences. Drugs targeting tissue cysts responsible for reactivations are a current priority.